Effective Mentoring to Improve Job Satisfaction among Beginner Teachers at South African Primary Schools - R. J. Nico Botha; Jean-Pierre Hugo (Research in Social Sciences and Technology, 2021)
Teachers leaving the profession before age of retirement is an ongoing problem in schools worldwide. While fewer teachers enter the profession each year, the number of teachers leaving the profession has increased. Many teachers listed lack of job satisfaction as a reason for leaving the education profession, while citing the lack of mentoring as a main cause of job dissatisfaction. This study explores the impact of an effective mentoring program at primary schools in the province of Mpumalanga, South Africa to support and improve job satisfaction among beginner teachers entering the profession. This study follows a quantitative approach, consisting of a Likert-scale questionnaire. The sample of the study was a number of 550 teachers (principals, deputy principals, heads of department, teachers and student teachers) from different races and cultures from 50 randomly selected state and private primary schools in Mpumalanga. After comparing the literature with the respondents' data, the researchers found that the development and implementation of a mentoring program in the province of Mpumalanga would positively impacts beginner teachers' job satisfaction, thus indicating a definite need for such a mentoring program.